2016
DOI: 10.1186/s12886-016-0218-0
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser hyaloidotomy in the management of Premacular Subhyaloid Hemorrhage

Abstract: BackgroundPremacular subhyaloid hemorrhage results in a sudden profound loss of vision. Among the modalities for its treatment, Nd:YAG laser hyaloidotomy is a non invasive method enabling rapid drainage of the obstructed macular area and improved vision within days. This study was aimed to evaluate the efficacy, visual outcome and complications following Nd:YAG laser hyaloidotomy for premacular subhyaloid hemorrhage.MethodsPatients with premacular subhyaloid hemorrhage of more than 3 disc diameters (DD) of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 20 publications
0
62
0
2
Order By: Relevance
“…In such a case, there is a likelihood that haemoglobin and iron have a toxic effect on retina [7]. Nd: YAG laser membranotomy is a widely used noninvasive method that usually improves vision acuity rapidly especially in cases of haemorrhage above 3 DD [8]. As regards complications, there is a small risk of epiretinal membrane, premacular cavity formation, and ILM thickening [9].…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, there is a likelihood that haemoglobin and iron have a toxic effect on retina [7]. Nd: YAG laser membranotomy is a widely used noninvasive method that usually improves vision acuity rapidly especially in cases of haemorrhage above 3 DD [8]. As regards complications, there is a small risk of epiretinal membrane, premacular cavity formation, and ILM thickening [9].…”
Section: Discussionmentioning
confidence: 99%
“…This feature has been reported very rarely in Eales disease. [ 14 15 ] Fig. 5 illustrates the fundus photograph of one of those two patients showing a premacular hemorrhage centered at the macula, around 2 disc diameters in size, surrounded by glistening striae, giving the clinical appearance of a “double ring.” A SD-OCT scan revealed that the outer ring (black arrows) was that of a subinternal limiting membrane (ILM) hemorrhage, while the inner ring (white arrows) was formed by hyperreflective deposits below the ILM that caused shadowing of the underlying retinal layers.…”
Section: Discussionmentioning
confidence: 99%
“…If possible, always drain from a region distant enough from the fovea along the inferior border where there is significant haemorrhagic elevation 7. Khadka et al 1 have recently reported an 86% success rate of Nd-YAG laser in management of premacular SHH in a study on 21 eyes with no complications at 6 months follow-up. They recommend that it is better to start with 5 MJ energy and then gradually increase by 1 MJ steps until 12 MJ.…”
Section: Discussionmentioning
confidence: 99%
“…Nd-YAG posterior hyaloidotomy is an established and promising treatment modality for rapid drainage of haemorrhage covering the macula 1. It is an inexpensive, effective and safe outpatient procedure.…”
Section: Introductionmentioning
confidence: 99%